Reversal of Congenital Hydrocephalus with Porencephalic Cyst and Neonatal Intracranial Hemorrhage in a 13-Year- Old: A Case Report Using a Neo Ayurveda Protocol-Miracle Drink - Raju, S. M. (Journal of Neonatal Surgery, 2026)
Background:Congenital hydrocephalus, porencephalic cyst formation, and neonatal intracranial hemorrhage are severe neurological conditions with high morbidity. MRI findings often reveal irreversible brain changes, including ventricular dilation, corpus callosum thinning, and hemispheric volume loss. Conventional management focuses on neurosurgical shunts and hematoma evacuation. Non-surgical neurological recovery in such cases is virtually unreported. Case Presentation:We report the case of a 13-year-old male with congenital hydrocephalus and neonatal intracranial hemorrhage. MRI revealed prominent asymmetric dilation of bilateral lateral ventricles, a large porencephalic cyst measuring 104 × 29 × 22 mm in the left frontal region, diffuse thinning of the corpus callosum (body and splenium), and left cerebral hemisphere volume loss. Clinically, the child presented with impaired hand coordination, abnormal gait, and neuromotor deficits since birth. Multiple attempts at management in allopathic, Ayurvedic, and neurological specialty centers (including NIMHANS, Bangalore) yielded poor prognosis, with surgery advised as the only option. Intervention:In July 2025, the patient was placed on a Neo Ayurveda -Miracle Drinks protocol, consisting of targeted herbal formulations (anti-aging, cardiovascular, and immune-care tonics) and a structured diet (flax-based meals, raw vegetable juices, high vegetable intake, restricted rice/wheat). Results:Within one month, the patient demonstrated restoration of hand coordination, normalization of gait, and enhanced neuromotor control, with marked improvement in daily functions. No surgical intervention was required, despite MRI evidence of longstanding congenital structural abnormalities. Conclusion:This case demonstrates the potential of Neo Ayurveda -Miracle Drinks protocols in achieving neurological recovery in congenital hydrocephalus with porencephalic cyst and neonatal ICH. Mechanisms likely include restoration of microcirculation, mitochondrial reactivation, detoxification, and neuroprotection. Controlled studies are needed to confirm reproducibility